Buildings environmental impacts' sensitivity related to LCA modelling choices of construction materials. (10th July 2017) - Häfliger, Ian-Frederic; John, Viola; Passer, Alexander; Lasvaux, Sebastien; Hoxha, Endrit; Saade, Marcella Ruschi Mendes; Habert, Guillaume
Abstract: The assessment of the environmental performance of buildings is now commonly using a life cycle approach, based on a growing number of databases and methods in Life Cycle Assessment (LCA). Recent studies have, however, highlighted the problems related to uncertainties in the LCA results. The aim of this study is to assess the sensitivity of construction materials to the different modelling choices in order to highlight their consequences at the building scale. In particular, we focused on the different modelling options in terms of database choices, system boundary definitions and replacement scenarios of building materials during the whole service life of the buildings. The assessment of uncertainties was conducted at two levels: the material or element level and the building level. The results clearly show the importance of these modelling choices. Variations on the overall assessment of buildings are significant, but the details at the material scale show that not all materials are similarly sensitive to these choices. We identified those materials that have a large contribution to the environmental impact of the buildings and which are also sensitive to different modelling choices. This can help for a better understanding of these modelling choices and can be used in upcoming regulations or public policies. Highlights: Impact of materials used during the building's life cycle have been assessed. We considered the different uncertainties related with the calculation method. Concrete has the main contribution to GWP but a low uncertainty in the calculation. Other materials are much more sensitive to calculation hypothesis. A particular attention should be taken on insulation and wooden materials.